2013
DOI: 10.1016/j.aap.2012.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Source of head injury for pedestrians and pedal cyclists: Striking vehicle or road?

Abstract: The potential effectiveness of vehicle-based secondary safety systems for the protection of pedestrians and pedal cyclists is related to the proportion of cases where injury arises by contact with the road or ground rather than with the striking vehicle. A detailed case review of 205 accidents from the UK On-the-Spot study involving vulnerable road users with head injuries or impacts indicated that contact with the road was responsible in 110 cases. The vehicle however was associated with a majority of more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In addition it has been shown that head injuries incurred by pedestrians in side impacts are mainly caused by impact with the road or ground rather than impact with the vehicle (Badea-Romero and Lenard, 2013), indicating the limitations of safety technology for this form of interaction between vehicles and vulnerable road users.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition it has been shown that head injuries incurred by pedestrians in side impacts are mainly caused by impact with the road or ground rather than impact with the vehicle (Badea-Romero and Lenard, 2013), indicating the limitations of safety technology for this form of interaction between vehicles and vulnerable road users.…”
Section: Methodsmentioning
confidence: 99%
“…In general it is agreed that the implementation of pedestrian detection and autonomous braking as part of an integrated active and passive system will have an important impact for the protection of vulnerable road users (Badea-Romero and Lenard, 2013;Searson et al, 2014) and this will help to tackle the problem of pedestrian accidents commonly caused by human error (Habibovic and Davidsson, 2012;Habibovic et al, 2013). Based on this evidence, governments and regulators, manufacturers, insurance companies and consumer rating organisations are already encouraging the implementation of pedestrian detection and AEB systems.…”
Section: Preprint Submitted To Accident Analysis and Prevention 19th Jumentioning
confidence: 99%
“…In addition, it has been determined that head injuries incurred by pedestrians in side impacts are mainly caused by impact with the road or ground rather than impact with the vehicle (Badea et al, 2013), indicating the limitations of safety technology for this form of interaction between vehicles and vulnerable road users.…”
Section: Fig 2 Risk Of Pedestrian Death As a Function Of Vehicle Immentioning
confidence: 99%
“…In cyclist fatalities, the head was the most frequently injured body region (Bambach et al, 2013;Matsui and Oikawa, 2015a). Badea-Romero and Lenard (2013) found that 69% of head injuries occurred from contact with the road or ground rather than with the striking vehicle. compared the rates of cyclist head injuries due to impact with vehicles or roads for age groups of 13-59 years, 60-64 years, 65-74 years, and over 75 years using Japanese accident data from 2009 to 2013.…”
Section: Introductionmentioning
confidence: 99%